2013
DOI: 10.3892/ol.2013.1104
|View full text |Cite
|
Sign up to set email alerts
|

Arg399Gln polymorphism of XRCC1 gene and risk of colorectal cancer in Kashmir: A case control study

Abstract: The aim of this study was to investigate the role of the XRCC1 Arg399Gln polymorphism in the susceptibility of a Kashmiri population to colorectal cancer (CRC). We investigated the genotype distribution of the XRCC1 gene in 130 CRC cases in comparison with that of 150 healthy subjects. There was no direct significant association between the XRCC1 genotypes and CRC; however, the Arg/Gln genotype was associated with an elevated risk of CRC (OR>1.47) and the Gln/Gln variant genotype was associated with an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Further, correlation for gender group versus stage of the disease-(stage III and Stage IV) with genotypes; we found no significance with this association between these parameters. This data were consistent with earlier reports on risk of cancer of the breast (Duell et al, 2001), bladder and lung (Ratnasinghe et al, 2001), thyroid carcer (Fard-Esfahani et al, 2011), bladder cancer (Mao et al, 2013), and colorectal cancer (Nissar et al, 2013). It is therefore obvious that XRCC1 codon 399 may be associated with altered function of the coding products and thus contribute to the individual's genetic susceptibility to lung cancer.…”
supporting
confidence: 91%
“…Further, correlation for gender group versus stage of the disease-(stage III and Stage IV) with genotypes; we found no significance with this association between these parameters. This data were consistent with earlier reports on risk of cancer of the breast (Duell et al, 2001), bladder and lung (Ratnasinghe et al, 2001), thyroid carcer (Fard-Esfahani et al, 2011), bladder cancer (Mao et al, 2013), and colorectal cancer (Nissar et al, 2013). It is therefore obvious that XRCC1 codon 399 may be associated with altered function of the coding products and thus contribute to the individual's genetic susceptibility to lung cancer.…”
supporting
confidence: 91%
“…Another study conducted by Nissar et al [18] among a Kashmiri population found a significant impact of the Trp/Trp and Arg/Trp genotypes on the development of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the heterozygous (399Arg/Gln) and variant (399Gln/Gln) genotypes of this SNP were significant risk factor for GIC in different populations including in Han Chinese for liver, gastric and colorectal cancers (Shen et al, 2000;Pan et al, 2011;Li et al, 2012;Zhao et al, 2012), US Caucasian for pancreatic cancer (Jiao et al, 2006) as well as Egyptian, Kashmiri, Korean and Japanese for colorectal cancer (Abdel-Rahman et al, 2000;Hong et al, 2005;Yin et al, 2012;Nissar et al, 2013). A recent meta-analysis also suggested that subjects with at least one 399Gln allele elevated the risk of hepatocellular cancer in Asian population (Liu et al, 2013) but other claimed that no direct association of this allele to colorectal cancer (Qin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%